Pancartas, grafitis y «memes»: simbología y memoria del 15-M entre lo nacional y transnacional - José Carlos Rueda Laffond; Carlota Coronado Ruiz (Cahiers de Civilisation Espagnole Contemporaine)
The 15-M, a protest movement emerged in Madrid in May 2011 as a reaction to the economic, social and political situation in Spain, became a catalyst for powerful symbolic expressions in which the discredit of institutions and representatives was revealed. In the following years, the memory of 15-M is constructed in an idealized way as if it were "a new Transition". The objective of this article is to study the practices of construction of the symbology around the 15-M carried out both in the mobilizations and in the media, as well as to establish the ways of configuring an idealized memory of those events.